Enhancing Mo:BiVO4 Solar Water Splitting with Patterned Au Nanospheres by Plasmon‐Induced Energy Transfer. Issue 5 (4th October 2017) - Kim, Jung Kyu; Shi, Xinjian; Jeong, Myung Jin; Park, Joonsuk; Han, Hyun Soo; Kim, Suk Hyun; Guo, Yu; Heinz, Tony F.; Fan, Shanhui; Lee, Chang‐Lyoul; Park, Jong Hyeok; Zheng, Xiaolin
Abstract: Plasmonic metal nanostructures have been extensively investigated to improve the performance of metal oxide photoanodes for photoelectrochemical (PEC) solar water splitting cells. Most of these studies have focused on the effects of those metal nanostructures on enhancing light absorption and enabling direct energy transfer via hot electrons. However, several recent studies have shown that plasmonic metal nanostructures can improve the PEC performance of metal oxide photoanodes via another mechanism known as plasmon‐induced resonant energy transfer (PIRET). However, this PIRET effect has not yet been tested for the molybdenum‐doped bismuth vanadium oxide (Mo:BiVO4 ), regarded as one of the best metal oxide photoanode candidates. Here, this study constructs a hybrid Au nanosphere/Mo:BiVO4 photoanode interwoven in a hexagonal pattern to investigate the PIRET effect on the PEC performance of Mo:BiVO4 . This study finds that the Au nanosphere array not only increases light absorption of the photoanode as expected, but also improves both its charge transport and charge transfer efficiencies via PIRET, as confirmed by time‐correlated single photon counting and transient absorption studies. As a result, incorporating the Au nanosphere array increases the photocurrent density of Mo:BiVO4 at 1.23 V versus RHE by ≈2.2‐fold (2.83 mA cm −2 ). Abstract : A hybrid Au nanosphere/molybdenum‐doped bismuth vanadium oxide (Mo:BiVO4 )photoanode interwoven in a hexagonal pattern to investigate the plasmon‐induced energy transfer effect on the photoelectrochemical performance of Mo:BiVO4 is described. This study finds that the Au nanosphere array not only increases the light absorption of the photoanode as expected but also improves both its charge transport and charge transfer efficiencies via plasmon induced energy transfer.